Compatibility Between Beauveria bassiana (Bals.) and Neem Extract against Brown Plant-Hopper (Nilaparvata lugens Stal.) - Nova Laili Wisuda; Tri Harjaka; Indah Dwi Prasetyaningrum (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2019)
Beauveria bassiana fungi and neem extract as botanical insecticide can be combined to get the synergizing effect to control brown planthopper (BPH). This study was conducted to determine the best combination between the spore density of B. bassiana and concentration of neem extract to control BPH effectively. The two factorial treatment consisted concentration of B. bassiana (106 Colony Forming Unit (CFU) and 107 CFU) and concentration of neem extract (5%, 10%, 15%), and control. The treatments were assigned in Completely Randomized Design with three replications. The data were analyzed using ANOVA and LSD at 5%. The test was conducted in vitro and bio assay of testing insects, BPH, was conducted using dipping method. B. bassiana was suitable with neem extract with T value ranged from 78.58- 90.38. The mortality of BPH occurred on day 5 after application. The highest mortality (91.67%) occurred on the treatment with B. bassiana 107 CFU + neem extract 10%. The shortest LT50 was found at the treatment of B. bassiana 106 CFU+ neem extract 15% (2.74 days) but not significantly different from B. bassiana 107 CFU + neem extract 15% (2.76 days). B. bassiana spores combined with neem extract are assumed to speed up the mortality of BPH by increasing the concentration.